Dose Volume Product (DVP) As Descriptor for Estimating Total Energy Imparted to Patient Undergoing CT Examination - Choirul Anam; Freddy Haryanto; Rena Widita; Idam Arif; Geoff Dougherty (Journal of Medical Physics and Biophysics, 2016)
The purpose of this study is to expand a descriptor for estimating the total energy imparted to a patient undergoing a CT examination and to investigate its relationship to the currently used descriptor. Estimating the total energy imparted to a patient has previously been characterized by dose length product (DLP). We propose a descriptor which we call the dose volume product (DVP), defined as the product of the size specific-dose estimate (SSDE) and the volume irradiated in the patient (V). We also present algorithm to automate the calculation of DVP. There are several steps in calculating the DVP: the first is to contour the patient automatically, the second is to calculate the area of patient in every single slice, the third is to calculate the volume of the radiated part of the patient, the fourth is to calculate the water equivalent diameter (DW) automatically, the fifth is to calculate the SSDE, and the last is to calculate the DVP. To investigate the effectiveness of the algorithm, we used it on images of phantoms and patients. The results of this study show that the automated calculations of DVP for both body and head phantoms were in good agreement with theoretical calculations. The differences between them were within 2%. DVP and DLP had a linear relationship with R2 = 0.971 (slope 1099 cm2, 95% confidence interval (CI), 1047 to 1157 cm2) and R2 = 0.831 (slope 248.6 cm2: CI, 237.6 to 259.7 cm2), for thorax and head patients respectively.